Identification of Hypermobile Scars on Tympanic Membrane Using Automatic Tympanometry - Dayalan Samuel J; Nandur VU; Joan D'Mello (Journal of All India Institute of Speech and Hearing, 1970)
Three subjects exhibited abnormal, atypical tympanographs when tested with  electromedics  86 AR Tympanometer. These tympanographs were similar to Ad  type, but with a clear notch. Repeated measures yielded similar findings. Ipsilateral reflexes were present in all these ears. Microscopic examination revealed fine, thin,  hypermobile  scars. Patients with flaccid tympanic membrane  yielded d type  tympanographs without a notch. The notched tympanographs obtained in tympanometer 86 AR seem to help in differential diagnosis.